UJI EFEKTIVITAS SISTEM DAN TEKNOLOGI AKUAKULTUR BERBASIS ASIMILASI LIMBAH AMONIA: GREEN WATER SISTEM, BIOFLOC, DAN AQUAPONIC SEBAGAI SOLUSI UNTUK BUDIDAYA IKAN GABUS (Channa striata) - Rizki, Rani Ria; Prariska, Donny; Lestari, Siti; Puteri, Rizki Eka; Selly, Selly Ratna Sari; Gutti, Guttifera (JARI : Jurnal Akuakultur Rawa Indonesia, 2023)
Snakehead fish cultivation in South Sumatra were still relatively small, but the market demand for snakehead fish were quite a lot to be used as a processed material or for treatment. Cultivating snakehead fish, the obstacles faced are ammonia waste (from leftover feed and feces) causing death in cultivated fish. Application of aquaculture technology systems that can minimize ammonia waste, namely the Green Water System, Biofloc, and Aquaponic. These three systems have the ability to absorb ammonia bicarbonate contained in snakehead fish farming waste. The purpose of this research is to find the best aquaculture system in reducing nitrogen waste and producing the highest snakehead fish productivity. This research used a completely randomized design (CRD) with 3 treatments and 3 replications, namely green water system (GWS), biofloc technology (BFT), and aquaponics (AP). The fish used were snakehead fish (Channa striata) measuring 7±05 cm, which was reared for 60 days, the test plant used in aquaponics was pakcoy, while the green water system used spirulina. Water quality data were analyzed descriptively using tables and pictures. Production performance data were analyzed for variance (ANOVA) with a 95% confidence interval. If the results are significantly different, then a further test is carried out using the Tukey test. The results obtained in this study included all treatments capable of creating optimal water quality in the form of ammonia, nitrite and nitrate for snakehead fish, and the GWS treatment produced the lowest ammonia, nitrite and nitrate values. The survival resulted in all treatments above 80%, with the best growth in weight and length obtained in the BFT treatment. The best feed conversion ratio was also produced by the BFT treatment by suppressing the lowest RKP value